Can aid buy foreign public support?: evidence from Chinese development finance - Wellner, Lukas; Dreher, Axel; Fuchs, Andreas; Parks, Bradley; Strange, Austin M. (Kiel working paper, 2022)
Bilateral donors use foreign aid to pursue soft power. We test the effectiveness of aid in reaching this goal by leveraging a new dataset on the precise commitment, implementation, and completion dates of Chinese development projects. We use data from the Gallup World Poll for 126 countries over the 2006–2017 period and identify causal effects with (i) an event-study model that includes high-dimensional fixed effects, and (ii) instrumental-variables regressions that rely on exogenous variation in the supply of Chinese government financing over time. Our results are nuanced and depend on whether we focus on subnational jurisdictions, countries, or groupings of countries.